Prevalence of thyroid dysfunction: Experience of a tertiary care centre in Kerala - Lakshminarayana Gopaliah R; Sheetal Lakshminarayana G; Nidhish P Sadanandan; Pramod M (International Journal of Medical Research and Review, 2016)
Background: There is limited data regarding the prevalence of thyroid disorders in India, and this is the first study to assess their prevalence in northern Kerala.Methods: All subjects who underwent blood sampling for estimation of thy-roid function tests (TFTs) on their initial visit to the EMS Memorial Cooperative Hospital and Research Centre, Perin-thalmanna (2009-2013) were included in the study.Results: The study population included 8179 subjects (Males: 3205, females: 4974), of ages from 1-94 (Mean-41.95) years of age. The overall prevalence rate of thyroid function abnormalities was 15.73%; more in females (16.91 %) than males (13.90%). The subclinical hypothyroidism (SCH) was the commonest thyroid abnormality (7.15 %) followed by overt hypothyroidism (4.2%), hyperthyroidism (2.77 %) and subclinical hyperthyroidism (SH) (1.6 %). The prevalence rate of hypothyroidism in different age groups was 2.81 % in 1-19, 3.53 % in 20-45 and 5.36 % in those ≥ 46 years respectively. The prevalence rate of SCH was highest (8.05 %) in the age group of 20-45 years followed by 6.74 % in ≥ 46 and 4.19 % in 1-19 years.Conclusions: The thyroid function abnormalities are common and the prevalence is higher in females than males. The prevalence rates of thyroid function disorders were 9.76%, 17.50 % and 15.05 % in age groups of 1-19, 20-45 and ≥ 46 years respectively. The SCH was the commonest abnormality, followed by overt hypothyroidism, hyperthyroidism and SH; first 3 conditions were more common in females than males, whereas last was common in males.